(untitled) (Fiep Bulletin - online, 2013)
The venous ulcer (UV) represents about 70% to 90% of the leg ulcers and is due mainly to chronic venous insufficiency (CVI). It has high relapse (66%) and constitutes the major problem in assisting individuals with IRC. In general, the pain of UV worsening the end of the day with the standing position and improves with the increase in the State. Ulcers deep in the region and ankle ulcers associated with small white atrophy are more painful. In this study aimed to characterize the scientific output, published between 2000 and July 2008, on pain in venous ulcers, on the grounds of VHL, PubMed, and ISI Web of Knowledge, on the type of presentation, research method, type of study, language, year of publication, rank and serial link. For that reason, were used as descriptors, the words "venous ulcers" and "pain" (venous ulcers and pain). 168 articles were selected: 03 in LILACS; 49 in MEDLINE; 45 Pubmed and 71 in the ISI Web of Knowledge. In SCIELO BDENF and publications were not found. Predominated the articles in the form of abstract (78.0%), quantitative method (72.6%), type a descriptive study (57.1%), English (98.2%) and the year 2007 (23, 8%), it was emphasized the treatment of UV (59.5%), followed by quality of life (15.5%) and clinical aspects of the patient and the UV (11.9%). Most of the studies was published in international journals such as Journal Wound Care (7.7%), Phlebology and Wound Repair Regen with 5.4% each. The journals have not reached national prominence (2.0%). We conclude that the pain has been investigated by UV assist the clinical diagnosis and interfere with the recovery and quality of life of individuals, therefore, needs is more studies that deal with the issue.